CLINICAL CASE OF CHRONIC VIRUS HEPATITIS C - Gavrilyuk, E. V.; Yatsyuk, E. V.; BоkatuevaV. V.; Bychkova, O. Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The article presents a clinical case of chronic virus hepatitis C with development myelodysplastic syndrome, a chronic anemic and hepatic encephalopathy. The authors discuss the clinical features, diagnosis, possible methods of medical treatment and prognosis.